Rose - Smith, Jeff; Vess, Charles (New York : Graphix, 2009)
Princess Rose musters up courage to face the dragon that threatens the small towns in the Northern Valley, only to discover the dragon is actually the Lord of the Locusts.
Briar & Rose -- Our brightest hope -- The ice queen -- We ask, teach -- Turn back -- Balsaad -- The warning -- The cave -- Into the night -- The master calls -- The pact -- Frozen -- Midnight -- The promise.
Originally published in the comic book Rose, c2000, 2001 and 2002.
Maps on endpapers.
330L
Keywords: Bone (Fictitious character); Dragons; Princesses; Graphic novels